2017
DOI: 10.1111/ijfs.13570
|View full text |Cite
|
Sign up to set email alerts
|

Determination and distribution of biogenic amines in bee pollen

Abstract: The natural decomposition of proteins yields peptides and amino acids, which are susceptible to further decay, resulting in formation of biogenic amines (BAs) in proteinaceous foods such as bee pollen (BP). However, excessive consumption of BAs will bring side effects, so it is vital to study the presence of BAs in BP. In this study, a sensitive and reliable ultra-high-performance liquid chromatography-tandem mass spectrometric method was used for the determination of 12 BAs in BP. Large variations in the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Even though the specificities of Neutrase and Protamex are not clearly defined (Dryáková, Pihlanto, Marnila, Čurda, & Korhonen, ), it is known that they are endoproteases characterized by their ability to hydrolyze internal peptides bonds (Liu et al, ), which preferentially release hydrophobic amino acids: phenylalanine, isoleucine, leucine, methionine, and valine (Dijk, Folkertsma, & Dekker, ). Although both fermentation and enzymatic hydrolysis are biotechnological processes recently employed for achieving a structural modification of bee‐pollen, Zhao et al () mention that microorganisms could lead to a decarboxylation of amino acids and a production of biogenic amines, organic nitrogenous compounds of low molecular weight formed during normal bacteria metabolism, which in excessive intake can be toxic for humans; their study showed an increase of up to five times in putrescine in fermented bee‐pollen compared to unfermented samples. Therefore, an enzymatic process may be more suitable for a technological transformation of bee‐pollen, but this needs to be thoroughly investigated in the future research.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the specificities of Neutrase and Protamex are not clearly defined (Dryáková, Pihlanto, Marnila, Čurda, & Korhonen, ), it is known that they are endoproteases characterized by their ability to hydrolyze internal peptides bonds (Liu et al, ), which preferentially release hydrophobic amino acids: phenylalanine, isoleucine, leucine, methionine, and valine (Dijk, Folkertsma, & Dekker, ). Although both fermentation and enzymatic hydrolysis are biotechnological processes recently employed for achieving a structural modification of bee‐pollen, Zhao et al () mention that microorganisms could lead to a decarboxylation of amino acids and a production of biogenic amines, organic nitrogenous compounds of low molecular weight formed during normal bacteria metabolism, which in excessive intake can be toxic for humans; their study showed an increase of up to five times in putrescine in fermented bee‐pollen compared to unfermented samples. Therefore, an enzymatic process may be more suitable for a technological transformation of bee‐pollen, but this needs to be thoroughly investigated in the future research.…”
Section: Resultsmentioning
confidence: 99%
“…The development of analytical methods for the detection of amines such as biogenic amines (BAs) has attracted considerable attention due to their critical analytes present in pharmaceutical, agricultural and food processing effluents [1–21] . BAs are biologically active monoamines or polyamines which are naturally produced in the human cells by the removal of the alpha carboxylic functional group present in the amino acid during an enzymatic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Biogenic amines are basic nitrogenous compounds that can be detected from various food, such as meat (Curiel et al, ), fish (Hwang et al, ; Kim, Mah, & Hwang, ), been pollen (Zhao et al, ), wine (Ouyang et al, ), and cheese (Pircher, Bauer, & Paulsen, ; Shalaby, Anwar, Sallam, & Emam, ). The common biogenic amines present in food are tyramine, histamine, cadaverine, putrescine, spermine, spermidine, tryptamine, and phenylethylamine (Curiel et al, ; Kim et al, ; Ouyang et al, ; Zhao et al, ). Excessive oral intake of these amines can induce vasoactive or psychoactive effect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, histamine can cause vomiting, fever, and hypertension. Hence, the presence of biogenic amine has a significant effect on food safety and human health (Shalaby et al, ; Zhao et al, ). Biogenic amine forms during food processing and storage due to microorganism growth (Shalaby et al, ).…”
Section: Introductionmentioning
confidence: 99%